2009
DOI: 10.1038/ejhg.2009.192
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ANKRD11 and ZNF778 as candidate genes for autism and variable cognitive impairment in the novel 16q24.3 microdeletion syndrome

Abstract: The clinical use of array comparative genomic hybridization in the evaluation of patients with multiple congenital anomalies and/or mental retardation has recently led to the discovery of a number of novel microdeletion and microduplication syndromes. We present four male patients with overlapping molecularly defined de novo microdeletions of 16q24.3. The clinical features observed in these patients include facial dysmorphisms comprising prominent forehead, large ears, smooth philtrum, pointed chin and wide mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
106
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(120 citation statements)
references
References 44 publications
12
106
2
Order By: Relevance
“…The individuals in our study also have ECAs with neurocognitive deficits and facial dysmorphisms (Table 2), as described in other studies. 42,47 CES caused by dup 22q11 is frequently associated with heart defects, particularly total anomalous pulmonary venous return or tetralogy of Fallot. 48 Although the critical region responsible for CVM has been ill-defined in children affected with CES, Riazi et al 49 have shown that overexpression of CECR1 causes heart defects in mice, including ASD.…”
Section: Discussionmentioning
confidence: 99%
“…The individuals in our study also have ECAs with neurocognitive deficits and facial dysmorphisms (Table 2), as described in other studies. 42,47 CES caused by dup 22q11 is frequently associated with heart defects, particularly total anomalous pulmonary venous return or tetralogy of Fallot. 48 Although the critical region responsible for CVM has been ill-defined in children affected with CES, Riazi et al 49 have shown that overexpression of CECR1 causes heart defects in mice, including ASD.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 When comparing the facial features of our patients with the previously described patients, some resemblance is noted: high forehead, a broad mouth and prominent chin. 1 Both patients also had a relatively small nasal bridge with mild synophrys and a bulbous nose tip, resembling patient 1 of the study of Willemsen et al at adult age. As in our patients, the stature of the reported patients is also relatively short compared with the other growth parameters.…”
mentioning
confidence: 99%
“…Last year, in this journal, Willemsen et al 1,2 presented four patients with an interstitial deletion of chromosome band 16q24.3. The overlapping phenotypical features provided evidence for a novel microdeletion syndrome characterized by variable levels of intellectual disability, autistic features (ASD) and facial dysmorphisms.…”
mentioning
confidence: 99%
“…Heterozygous deletions at 16q24.3 that contain the ANKRD11 gene were also described in patients with ID, autistic spectrum disorder, and in some cases with brain anomalies, a clinical phenotype overlapping with KBG syndrome (Marshall et al 2008;Willemsen et al 2010;Handrigan et al 2013;Isrie et al 2012;Sacharow et al 2012;Khalifa et al 2013;Miyatake et al 2013).…”
mentioning
confidence: 99%
“…ANKRD11 localizes mainly to the nuclei of neurons and accumulates in discrete inclusions when neurons are depolarized (Sirmaci et al 2011). Thus, it is not surprising that ANKRD11 mutations lead to a neurobehavioral phenotype (Willemsen et al 2010;Handrigan et al 2013;Sacharow et al 2012;Spengler et al 2013). However, how ANKRD11 mutations act at the molecular level remains unknown.…”
mentioning
confidence: 99%